The analysis and implementation of remote production monitoring system in manufacturing industries - Wijianto, Wijianto; Nadiatul Azwa, Nadiatul Azwa; Ahmad, Aishah; Ibrahim, Rasidi; Samsudin, Nor Azah; Mohamad, Norman (2020)
The emergence of the fourth industrial revolution (IR4.0) turns manufacturing process into digital environment. In this transition, new technology especially the Internet of Things (IoT) play an important part in the global market rivalry. In order to shift manufacturing companies to the Internet of Things, it is crucial to connect their activities to the digital world using smart sensor systems. To overcome with this problem, this project presents a remote monitoring system for shop-floor and based on the IoT standard. This project is also about analyzing and developing a Remote Production Manufacturing System (PMS) framework and online tool condition monitoring system according to the Internet of things requirements (IR 4.0). The system is designed to establish a data acquisition and monitor the production shop floor remotely. For further processing, visualization and analyses, the monitored data are transferred to a cloud server using MDCMAX solution. The developed system follows the IoT model to connect physical manufacturing with the cyber world and offer integration capabilities with existing industrial manual systems. Monitoring device installation is validated using a CNC milling machine on an industrial laboratory shop floor.